A pedagogical paradigm for enhancing motivation and mastery in history education: Exploring the efficacy of Ehsond intervention - Nurul Asyikin Hassana; Anizah Mohd Salleh; Zainun Mustafa; Siti Zahrah Mahfood; Dg Junaidah Awang Jambol; Murihah Abdullah (ResearchGate, 2024)
Problems in the subject of History are always discussed at various levels. Issues such as a lack of interest in the subject of History, feelings of stress, the need to memorize a multitude of facts, as well as issues regarding traditional teaching methods, textbooks, classroom management, innovation, and teaching aids, are also extensively debated. These problems have triggered numerous reactions and solutions from multiple parties, each with its approach to solving them. Thus, this article aims to assist the subject of History by providing an alternative solution in the field of intervention as one of the systematic methods of teaching History. Hence, the objectives of this study were to explore the use of the Ehsond Intervention in providing motivation and to explore the impacts of using the Ehsond Intervention on the subject of History. This study involved three informants who had been selected in a focused manner as study samples by employing a qualitative method with a case study design. The instruments used were observations, interviews, and reflection notes. The study's findings revealed that the Ehsond Intervention method was a tool that could help students master the subject of history and boost student motivation to learn the subject.